Childhood adversity and subsequent mental health status in adulthood: screening for associations using two linked surveys. (25th February 2015) - Patten, S. B.; Wilkes, T. C. R.; Williams, J. V. A.; Lavorato, D. H.; el-Guebaly, N.; Wild, T. C.; Colman, I.; Bulloch, A. G. M.
Abstract : Aims: Accumulating evidence links childhood adversity to negative health outcomes in adulthood. However, most of the available evidence is retrospective and subject to recall bias. Published reports have sometimes focused on specific childhood exposures (e.g. abuse) and/or specific outcomes (e.g. major depression). Other studies have linked childhood adversity to a large and diverse number of adult risk factors and health outcomes such as cardiovascular disease. To advance this literature, we undertook a broad examination of data from two linked surveys. The goal was to avoid retrospective distortion and to provide a descriptive overview of patterns of association. Methods: A baseline interview for the Canadian National Longitudinal Study of Children and Youth collected information about childhood adversities affecting children aged 0–11 in 1994. The sampling procedures employed in a subsequent study called the National Population Health Survey (NPHS) made it possible to link n = 1977 of these respondents to follow-up data collected later when respondents were between the ages of 14 and 27. Outcomes included major depressive episodes (MDE), some risk factors and educational attainment. Cross-tabulations were used to examine these associations and adjusted estimates were made using the regression models. As the NPHS was a longitudinal study with multiple interviews, for most analyses generalized estimating equations (GEE) were used. As there were multiple exposures and outcomes, a statistical procedure to control the false discovery rate (Benjamini–Hochberg) was employed. Results: Childhood adversities were consistently associated with a cluster of potentially related outcomes: MDE, psychotropic medication use and smoking. These outcomes may be related to one another since psychotropic medications are used in the treatment of major depression, and smoking is strongly associated with major depression. However, no consistent associations were observed for other outcomes examined: physical inactivity, excessive alcohol consumption, binge drinking or educational attainment. Conclusions: The conditions found to be the most strongly associated with childhood adversities were a cluster of outcomes that potentially share pathophysiological connections. Although prior literature has suggested that a very large number of adult outcomes, including physical inactivity and alcohol-related outcomes follow childhood adversity, this analysis suggests a degree of specificity with outcomes potentially related to depression. Some of the other reported adverse outcomes (e.g. those related to alcohol use, physical inactivity or more distal outcomes such as obesity and cardiovascular disease) may emerge later in life and in some cases may be secondary to depression, psychotropic medication use and smoking.